IMPROVING CREATIVITY THROUGH PROBLEM-BASED LEARNING: A PHYSICS TEACHING MATERIALS AND INSTRUMENT DEVELOPMENT WITHIN THE CAMBRIDGE FRAMEWORK - Ade Sukandi Novita; Dwikoranto Dwikoranto (MO.RI Publishing, 2025)
This study aims to develop PBL teaching materials and instrument to improve students’ creative thinking skills in the topic electrical circuits. This research method’s uses a 4-D development model divided to 4 stages, which are Define, Design, Develop, and Disseminate. the study identified students' difficulties in understanding abstract concepts and their low creative thinking, especially in flexibility and elaboration. The developed materials included a lesson plan, worksheet, and creative thinking test. Validation results showed that all materials and instrument developed achieved a “Very Valid” category and suitable to implement during learning process. Effectiveness was tested through pretest and posttest analysis, yielding an average n-gain of 0.73 (high category), with particularly strong improvements in fluency, flexibility, and elaboration.